1972
DOI: 10.1039/p29720001607
|View full text |Cite
|
Sign up to set email alerts
|

The vibrational spectra of compounds containing the dimethylamino-group. Part II. p-NN-dimethylaminobenzonitrile and the N-methyltoluidines

Abstract: The i.r. and Raman spectra of p-chlorobenzonitrile and p-NN-dimethylaminobenzonitrile have been recorded in the range 4000-1 0 cm-I. The fundamental vibrational frequencies of these systems have been computed. On the ' r Part 1, A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 0 publications
4
34
0
Order By: Relevance
“…16, 37 Since the favored excited-state geometry of the amino nitrogen is also planar, due to the CT-induced radical cation character, ∆Q e will be reduced by N-phenyl substitution. The changes in the amino wagging angle and the electronic nature of the amino nitrogen might affect the C Ph -N stretching, 38 which has a frequency of ca. 1300 cm Ϫ1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16, 37 Since the favored excited-state geometry of the amino nitrogen is also planar, due to the CT-induced radical cation character, ∆Q e will be reduced by N-phenyl substitution. The changes in the amino wagging angle and the electronic nature of the amino nitrogen might affect the C Ph -N stretching, 38 which has a frequency of ca. 1300 cm Ϫ1 .…”
Section: Discussionmentioning
confidence: 99%
“…1300 cm Ϫ1 . 9,10, 38 In addition to the amino group, the introduction of N-phenyl groups might also perturb the structure of the stilbene moiety, particularly the C᎐ ᎐ C bond length and the C e -Ph torsional angle. It is known that the length of the ethylene group increases in the excited state due to the reduction in doublebond character.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we found it helpful to compare the Raman spectra of CV and MG to the normal coordinate analysis of N,N-dimethylaminobenzonitrile (DMABN), published in Ref. 11.…”
Section: Methodsmentioning
confidence: 99%
“…The ground state structure of the crystalline and gas phase DMABN has been determined by X-ray di †raction analysis11 and microwave spectroscopy,12 respectively. Vibrational spectra and vibrational analysis of the ground state of DMABN have been carried out by Gates et al 13 and Schneider et al14 using empirical and semi-empirical force Ðeld methods, respectively, and gave conÑicting assignments of several bands. In a recent publication, Okamoto et al 15 reported the same analysis based on both empirical and quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 99%